Influence of Institutional Support And Entrepreneurial Self-Efficacy On Business Performance Of Women Entrepreneurs In Medan City - Arika Ulayya Harahap; Yasmin Chairunisa Muchtar (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This study aims to determine and analyze institutional support and entrepreneurial self-efficacy in achieving business performance of women entrepreneurs in Medan City. The population of this study was 150 women entrepreneurs in Dinas Perdagangan Medan City and the number of sample was 60 women entrepreneurs with a random sampling technique. The research data were obtained from interviews and distributing research questionnaires to women entrepreneurs in Dinas Perdagangan Medan City. The analysis technique uses multiple linear regression analysis. The results of this study indicate that simultaneously institutional support and entrepreneurial self-efficacy has a positive and significant effect on institutional support and entrepreneurial self-efficacy of women entrepreneurs in Dinas Perdagangan Medan City. The results of the research partially showed that institutional support and entrepreneurial self-efficacy each had a positive and significant effect on the business performance of women entrepreneurs in Dinas Perdagangan Medan City